Sistem Pendukung Keputusan Kinerja Dosen Menggunakan Metode Analytical Network Process (Anp) Pada Universitas - Nahot Frastian; Dona Katarina; Heriyati Heriyati (LPPM, 2018)
Information technology continues to innovate and has the opportunity to grow further. One of the developments in information technology can be used as a means of performance evaluation is the Analytical Network Process (ANP) method. The assessment technique in this study is based on an assessment technique with a weighting assessment rule with a percentage distribution and a clearer weighting assessment rule. The Analytic Network Process (ANP) and Super Decision Software methods can be used to assess the performance of lecturers at the University. Lecturer performance appraisal process consists of several assessment criteria namely Pedagogy, Professional, Personality, and Social. The method used in sampling is a purposive sample (intentionally) with the best 5 to 10 lecturers that will be assessed by students. Respondents in this case students were taken randomly. Lecturer performance is weighted to produce a percentage for lecturer performance appraisal. This research resulted in a system in the form of percentage assessment or performance ranking of lecturers, this needs to be done so that research can produce an optimal decision that can be used as a decision support system as an assessment of the performance of lecturers at the university.Keywords: decision support system, analytical network process (ANP), lecturer.